2011
DOI: 10.2478/v10011-010-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin in Healthy Women and Breast Cancer Patients

Abstract: Kratak sadr`aj: Serumski tumorski markeri su zna~ajno analiti~ko sredstvo u proceni kancera dojke. Trenutno najzna~ajniji markeri raka dojke, CA 15-3 antigen i CEA, su posebno zna~ajni u pra}enju pacijenata sa uznapredovalom bole{}u. Feritin pripada grupi drugih molekula koji mogu biti potencijalno interesantni u praksi i ~ija je koncentracija tako|e promenjena u serumu pacijenata sa tumorima dojke. U ovoj studiji serumska koncentracija feritina je odre|ena u grupi pacijenata sa kancerom dojke pre hirur{ke int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…This well confirmed by a number of retrospective studies which have also demonstrated that the increase in serum ferritin level is associated with the higher risk of SGA in pregnancies with beta thalassemia intermedia (Gaspar, Ortega, & Moreiras, 1993;Origa et al, 2010;Uberos, 2000;Višnjevac, Segedi, Ćurčić, Višnjevac, & Stajić, 2011). Pregnancies complicated by IUGR have higher serum ferritin level due to decrease in ferritin and iron absorption by placenta (Bashiri, Burstein, Sheiner, & Mazor, 2003;Cogswell, Parvanta, Ickes, Yip, & Brittenham, 2003;Ćujić D, 2011;Haram, Svendsen, & Myking, 2007;Ronnenberg et al, 2004;Uberos, 2000).…”
Section: Discussionmentioning
confidence: 76%
“…This well confirmed by a number of retrospective studies which have also demonstrated that the increase in serum ferritin level is associated with the higher risk of SGA in pregnancies with beta thalassemia intermedia (Gaspar, Ortega, & Moreiras, 1993;Origa et al, 2010;Uberos, 2000;Višnjevac, Segedi, Ćurčić, Višnjevac, & Stajić, 2011). Pregnancies complicated by IUGR have higher serum ferritin level due to decrease in ferritin and iron absorption by placenta (Bashiri, Burstein, Sheiner, & Mazor, 2003;Cogswell, Parvanta, Ickes, Yip, & Brittenham, 2003;Ćujić D, 2011;Haram, Svendsen, & Myking, 2007;Ronnenberg et al, 2004;Uberos, 2000).…”
Section: Discussionmentioning
confidence: 76%
“…Ćujić 등의 연구에서는 (7) 조기 유방암 환자와 진행된 유방암 환자의 두 군 모두 정상 폐경 전 여성보다 ferritin 값이 증가되어 있었고 정상 대조군 250명과 조기 유방암 환자 229명의 ferritin 수치를 비교한 Jacobs의 연 구에서도 유방암 환자군이 정상 대조군보다 유의하게 ferritin 수치가 높았다 (18). 115명의 폐암 환자와 74명의 양성 폐질환 환자를 대상으로 한 연구에서 양성 폐질환 환자보다 폐암 환자의 혈청 ferritin 수치가 유의하게 높 았고 (11), Ito 등에 의해 진행된 ferritin과 자궁경부암과의 연구도 (13) Table 4).…”
Section: 서 론unclassified
“…Thus, breast cancer may exist for a long period as either a non invasive disease or an invasive but non metastatic disease. [4][5][6] These facts have significant clinical ramifications. 7 Rising numbers of cases of breast cancer in India are the more young ladies affected.…”
Section: Introductionmentioning
confidence: 99%